Exploring critical factors influencing the diffusion of electric vehicles in China: A multi-stakeholder perspective. (December 2017) - Liu, Hu-Chen; You, Xiao-Yue; Xue, Yi-Xi; Luan, Xue
Abstract: Electric vehicles (EVs) have received significant global attention due to the high energy efficiency and low pollutant emissions. In recent years, the Chinese government has allocated considerable funding and taken a number of legislative and regulatory steps for promoting the deployment of EVs. However, the increasing trend of EV adoption is not satisfying. In this paper, we investigate the factors that influence the diffusion of EVs in China from a multi-stakeholder perspective. Considering that decision makers' evaluation information is often imprecise and there can be significant dependence and feedback among influencing factors, a three-phase framework based on 2-tuple linguistic method and decision making trial and evaluation laboratory (DEMATEL) is proposed. First, a set of specific influencing factors is identified through a literature review and expert interviews. Second, direct relations of the influencing factors are evaluated using the 2-tuple linguistic method. Third, the critical factors influencing the diffusion of EVs in China are determined via the DEMATEL technique. According to the results of an empirical case study, 'technological level', 'policies and regulations', 'consumer acceptance and expectation', 'price and models', and 'market structure and competition' are critical factors influencing the diffusion of EVs in the Chinese market, which should be emphasized by the government and automakers for the benefits of EV development.